The Governance Of Tourism Village In Sipirok Subdistrict South Tapanuli Regency - LUBIS, Anwar Fuad Alamsyah (PT Keberlanjutan Strategis Indonesia, 2023)
A tourist village is an alternative tourism development whose management relies on the values of socio-cultural wisdom, economy, building forms, history, natural wealth and village human resources. Discussions and practices of tourism villages are trending both globally, nationally and regionally. South Tapanuli Regency is one of the areas that has implemented a tourism village policy. There are 18 tourist villages in South Tapanuli Regency and 6 of them are in Sipirok District. The purpose of this study was to analyze and compare the governance of 6 tourist villages in Sipirok District, South Tapanuli Regency. This study uses a qualitative descriptive method and data collection techniques are observation, interviews, and documentation. The results of the study show that the coordination between the tourism office, village government, and Pokdarwis is not intense, resulting in different perceptions in the management of tourist villages. Several villages cooperate and coordinate with institutions outside the government so that they are assisted in managing tourism. Community participation can be seen when the village has found a tourist target that is in accordance with the existing tourism potential in the village.